Creutzfeldt-Jakob disease surveillance in Australia: update to 31 December 2024 - Stehmann, Christiane; Senesi, Matteo; Sarros, Shannon; McGlade, Amelia; Lewis, Victoria; Agustina, Priscilla; Barber, Daniel; Klug, Genevieve; Holper, Sarah; McLean, Catriona; et al. (Communicable Diseases Intelligence, 2025)
Nationwide surveillance of Creutzfeldt-Jakob disease (CJD) and other human prion diseases is performed by the Australian National Creutzfeldt-Jakob Disease Registry (ANCJDR). National surveillance encompasses the period since 1 January 1970, with prospective surveillance occurring from 1 October 1993. Over this prospective surveillance period, considerable improvements have been developed in pre-mortem diagnostics; in the delineation of new disease subtypes; and in heightened awareness of prion diseases in healthcare settings. Surveillance practices of the ANCJDR have evolved and adapted accordingly. This report summarises the activities of the ANCJDR during 2024. Since the ANCJDR began offering diagnostic cerebrospinal fluid (CSF) 14-3-3 protein testing in Australia in September 1997, the annual number of referrals has steadily increased. In 2024, a total of 760 domestic CSF specimens were referred for diagnostic testing and 88 persons with suspected human prion disease were formally added to the national register. As of 31 December 2024, approximately half (42) of the 83 initial case notifications for 2024 remain classified as ‘incomplete’; 21 cases were classified as ‘definite’ and 17 as ‘probable’ prion disease; three cases were excluded through neuropathological examination. For 2024, seventy-two percent of all suspected human-prion-disease-related deaths in Australia underwent neuropathological examination. No cases of variant or iatrogenic CJD were identified in Australia during 2024.